Heat and smoke pre‐treatment of seeds to improve restoration of an endangered Mediterranean climate vegetation type - Hall, Stuart A.; Newton, Rosemary J.; Holmes, Patricia M.; Gaertner, Mirijam; Esler, Karen J. (Austral ecology, 2017)
Invasive alien plants impact ecosystems, which often necessitates their removal. Where indigenous species recovery fails following removal alone, an active intervention involving reintroduction of seed of native species may be needed. This study investigated the potential for a combination of the fire cues of smoke and heat as a pre‐treatment of seeds in breaking dormancy and facilitating increased germination. Species were selected to represent different functional types within Cape Flats Sand Fynbos; a fire‐prone, critically endangered vegetation type in South Africa. Seeds were exposed to either a heat pulse (temperatures between 60 and 300°C for durations of between 30 s and 20 min) or dry after‐ripening (1 or 2 months at milder temperatures of 45°C or less). Thereafter, seeds were soaked in smoke solution for 18 h and subsequently placed on agar at 10/20°C for germination. Most species fell into one of two main groups: Seed germination in the first group was greatest following a lower temperature (60°C) heat pulse, an extended period of mild temperature (20/40°C or 45°C) exposure, or no pre‐treatment with heat. Seed germination in the second group was promoted after brief exposure to higher (100°C) temperatures. No germination occurred in any species following heat treatments of 150°C or higher. Species which responded better to higher temperatures were mainly those possessing physical dormancy, but seed morphology did not correlate with germination success. This study showed that heat stimulation of seeds is more widespread in fynbos plant families than previously known and will enable the development of better seed pre‐treatment protocols before large‐scale sowing as an active restoration treatment after alien plant clearing.